1995
DOI: 10.1029/95jb00150
|View full text |Cite
|
Sign up to set email alerts
|

Lateral variations in mantle velocity structure and discontinuities determined from P, PP, S, SS, and SSSdS travel time residuals

Abstract: On the basis of P, PP, S, SS arrival times and SS ‐ S410S, SS ‐ S660S differential times, we construct models of mantle P and S velocity structure and boundary topography of the 410‐km and 660‐km discontinuities. Events from the catalog of the International Seismological Centre (ISC) are relocated relative to the International Association of Seismology and Physics of the Earth's Interior 1991 (IASP91) velocity model using both P and S arrival times. The arrival times are corrected for ellipticity and the PP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 55 publications
1
48
0
Order By: Relevance
“…[1994] was extended to include internally reflected PP and SS phases as well as underside reflections off the 410 and 660 km discontinuities to examine the possible trade-off between volumetric heterogeneity and the boundary deflections on these interfaces [Vasco et al, 1995a]. They found that P and S velocity estimates are not significantly contaminated by boundary topography of the order of 30 km.…”
Section: Introductionmentioning
confidence: 99%
“…[1994] was extended to include internally reflected PP and SS phases as well as underside reflections off the 410 and 660 km discontinuities to examine the possible trade-off between volumetric heterogeneity and the boundary deflections on these interfaces [Vasco et al, 1995a]. They found that P and S velocity estimates are not significantly contaminated by boundary topography of the order of 30 km.…”
Section: Introductionmentioning
confidence: 99%
“…To improve sampling, Vasco and co workers Vasco et al 1993Vasco et al , 1994Vasco et al , 1995a used ISC data from a large range of seismic phases. Their most recent P wave model is based on P, PP, PKP^B, PKPBc, PKPr)F, and PcP (absolute) travel time residuals [Vasco and Johnson, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Although most travel-time tomography studies use the first P-and S-wave arrivals, some researchers have used later-phase data (i.e., reflected and converted waves) to determine velocity tomography at both the local scale (e.g., Zhao et al 1992Zhao et al , 2005Xia et al 2007;Gupta et al 2009) and the global scale (e.g., Vasco et al 1995, Zhao 2001bZhao et al 2013). It is found that the later-phase data are very useful in tomographic imaging, because they sample the Earth's structure in areas which are not well sampled by the first P-and S-waves.…”
Section: Velocity Tomography Methodsmentioning
confidence: 99%